Juridical Analysis of Dismissal of Village Heads Affected by Adultery Cases (Case Study Decision Number: 3/G/2022/PTUN.SMG) - Nadia Salsabila Rahma; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2023)
In conducting this research, the research objective was to describe how the arrangements regarding the dismissal of village heads in the Village Law no. 6 of 2014 and what are the legal considerations of the judges of the Semarang State Administrative Court in deciding the Decision Number: 3/G/2022/PTUN.SMG case concerning the Dismissal of the Village Head in Karangtengah Village who used a normative juridical method in his analysis. This research has the following results: 1. The dismissal of the village head has been regulated in Article 40 of Law no. 6 of 2014 concerning Villages, when viewed from the case in the decision above the Village Head resigned because he was dismissed by the Regent for violating the prohibition stated in the law. 2. According to the PTUN decision, because he had committed the crime of adultery, which in this case violated Article 29 of Law No. 6 of 2014 concerning Villages, namely disturbing a group of people, the Village Head was dismissed from his position. In terms of deciding on the decision, the judge has considered through laws and regulations and aspects such as juridical, philosophical, and sociological aspects. As a result, the object of dispute in the decision is considered valid and legally enforceable.